2012
DOI: 10.1096/fasebj.26.1_supplement.1051.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gum Arabic on oxidative stress and inflammation in adenine–induced chronic renal failure in rats

Abstract: Inflammation and oxidative stress are known to be involved in the pathogenesis of chronic kidney disease in humans, and in chronic renal failure (CRF) in rats. The aim of this work was to study the role of inflammation and oxidative stress in adenineinduced CRF and the effect thereon of the purported nephroprotective agent gum arabic (GA). Rats were divided into four groups and treated for 4 weeks as follows: control, adenine in feed (0.75%, w/w), GA in drinking water (15%, w/v) and adenine+GA, as before. Urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The findings of the present study demonstrated that Gum acacia treatment improved the measured kidney function parameters, according to biochemical findings and hematological results. This is comparable to the previously described finding lung [6] [16] . It is widely known that oxidative stress results from an imbalance between increases in reactive oxygen species (ROS) generation a subsequent decrease in the body's natural antioxidant defence mechanisms causes oxidative stress [17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of the present study demonstrated that Gum acacia treatment improved the measured kidney function parameters, according to biochemical findings and hematological results. This is comparable to the previously described finding lung [6] [16] . It is widely known that oxidative stress results from an imbalance between increases in reactive oxygen species (ROS) generation a subsequent decrease in the body's natural antioxidant defence mechanisms causes oxidative stress [17].…”
Section: Discussionsupporting
confidence: 92%
“…The measured data demonstrated that adenine administration dramatically increased oxidative stress and lipid peroxidation, followed by a considerable drop in antioxidant enzymes. In previous experiments, research team found that lipid peroxidation levels rose in the kidney [19] , lung [6] and cecum [16]. Homogenates of mice treated with adenine, followed by a decline in the antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…demonstrated that gum arabic has anti-inflammatory and anti-oxidative effects in chronic renal failure. 63 It is also shown that gum arabic modifies anti-inflammatory cytokine in mice fed with high fat diet induced obesity. 64 Another research reported that gum arabic reduces inflammation, oxidative, and nitrosative stress in the gastrointestinal tract of mice with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%